Polyphosphate Stabilizes Protein Unfolding Intermediates as Soluble Amyloid-like Oligomers. Issue 21 (19th October 2018) - Yoo, Nicholas G.; Dogra, Siddhant; Meinen, Ben A.; Tse, Eric; Haefliger, Janine; Southworth, Daniel R.; Gray, Michael J.; Dahl, Jan-Ulrik; Jakob, Ursula
Abstract: Inorganic polyphosphate (polyP) constitutes one of the most conserved and ubiquitous molecules in biology. Recent work in bacteria demonstrated that polyP increases oxidative stress resistance by preventing stress-induced protein aggregation and promotes biofilm formation by stimulating functional amyloid formation. To gain insights into these two seemingly contradictory functions of polyP, we investigated the effects of polyP on the folding model lactate dehydrogenase. We discovered that the presence of polyP during the thermal unfolding process stabilizes folding intermediates of lactate dehydrogenase as soluble micro-β-aggregates with amyloid-like properties. Size and heterogeneity of the oligomers formed in this process were dependent on the polyP chain length, with longer chains forming smaller, more homogenous complexes. This ability of polyP to stabilize thermally unfolded proteins even upon exposure to extreme temperatures appears to contribute to the observed resistance of uropathogenic Escherichia coli toward severe heat shock treatment. These results suggest that the working mechanism of polyP is the same for both soluble and amyloidogenic proteins, with the ultimate outcome likely being determined by a combination of polyP chain length and the client protein itself. They help to explain how polyP can simultaneously function as general stress-protective chaperone and instigator of amyloidogenic processes in vivo . Graphical abstract: Highlights: PolyP stabilizes thermal unfolding intermediates of LDH as soluble oligomers of defined size and shape. PolyP–LDH intermediates exert features of amyloid-like β-aggregate. PolyP maintains refolding competence of LDH upon incubation at near-boiling temperatures. PolyP production protects bacteria against extreme temperature stress.